Literature Review: The Effect of Work Stress on Generation Z Employee Performance with Work–Life Balance as a Mediating Variable at KOPDES Coffee Shop Bangkalan - Aulia Rahma Yanti; Fyo Gebina; Yessica Pauline Riani Purba; Dimas Sena Putra; Mochammad Isa Anshori (PT. Sativa Publishing Group, 2025)
This study aims to analyze the effect of work stress on the performance of Generation Z employees, with work life balance serving as a mediating variable at Kopdes Coffee Shop Bangkalan. This research employs a qualitative approach with a descriptive case study design. Data were collected through semi-structured interviews with the business owner and five Generation Z employees selected using purposive sampling. The data were analyzed using thematic analysis to identify patterns and themes related to work stress, work life balance, and employee performance. The findings indicate that employees do not experience excessive work stress due to the support provided by the business owner through open communication and efforts to maintain employees’ emotional well-being. However, external pressures such as family conflicts and financial issues are the main sources of stress affecting performance. Work life balance is proven to play a significant role in maintaining employee performance stability. Policies such as fair shift distribution, designated days off, and flexible working hours enable employees especially those belonging to Generation Z to balance work with personal activities such as education and sidejobs.